5-Nitro-isophthalic acid based Co(II)-coordination polymers: Structural diversity tuned by imidazolyl ligands, efficient dye degradation and luminescence sensing. (15th September 2021) - Yang, Yuting; Tu, Changzheng; Liu, Zining; Wang, Jianling; Yang, Xiaoli; Cheng, Feixiang
Graphical abstract: Three new coordination polymers with 2D and 3D architectures formed by H2 nip and different configurations of imidazolyl ligands were structurally characyerized. Complex 1 is an effective and stable photocatalyst for the photodegradation of MEB. Complexes 1 and 3 reveal promising luminescent sensors towards Fe 3+ ion. Abstract: Three new coordination polymers with the formulas of [Co(nip)(bibp)]·0.5(H2 O)n (1 ), [Co(nip)(bimh)]n (2 ), [Co(nip)(titb)]·H2 On (3 ) (H2 nip = 5-nitro-isophthalic acid, bibp = 4, 4′-bis(imidazol-1-yl)biphenyl, bimh = 1, 6-bis(imidazol-1-yl)-hexane, titb = 1, 3, 5-Tris(imidazol-1-ylmethyl)-2, 4, 6-trimethylbenzene) were synthesized and structurally characyerized. Compound 1 has 2D (3 6 )-hxl layer topology structure. Compound 2 shows a two-fold interpenetrating 2D 4 4 square-grid planar network (4 4 -sql ) in which 1D [Co(nip)]n chains are interconnected by bimh ligand. Compound 3 possesses a 3D (3, 5)-connected topological structure with a (6 3 )(6 9 ·8) Schläfli symbol. Furthermore, the heterogeneous catalytic oxidation activity of 1 toward methylene blue in the presence and abserence of H2 O2 are investigated in aqueous solution. And both compounds 1 and 3 exhibit selective sensing toward Fe 3+ through the luminescent quenching experiments.